2023
DOI: 10.1186/s13256-023-03789-1
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of metronidazole vaginal tablets on vaginal bacteria-related postoperative complications with total laparoscopic hysterectomy

Abstract: Background The use of total laparoscopic hysterectomy is increasing. However, as with conventional abdominal hysterectomy, vaginal bacteria-related postoperative complications need to be managed in total laparoscopic hysterectomy. Therefore, we started to combine metronidazole vaginal tablets with intravenous administration of cephem antibiotics immediately before starting surgery to reduce complications. To evaluate the effect of this combination, and to determine the risk factors for these co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The representative characteristics of the procedures are as follows. 1) In our hospital, as described in the previous report [20] , in addition to intravenous 1 g cefazolin administered immediately before starting the operation, we added metronidazole vaginal tablets before and after the operation. As bowel preparation, all patients received two tablets of sennoside (24 mg) one day before operation, though vaginal culture examination were not performed before operation.…”
Section: Methodsmentioning
confidence: 99%
“…The representative characteristics of the procedures are as follows. 1) In our hospital, as described in the previous report [20] , in addition to intravenous 1 g cefazolin administered immediately before starting the operation, we added metronidazole vaginal tablets before and after the operation. As bowel preparation, all patients received two tablets of sennoside (24 mg) one day before operation, though vaginal culture examination were not performed before operation.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent non-randomized retrospective study, Okamura et al reported that vaginal metronidazole 250 mg tablets before and immediately after total laparoscopic hysterectomy resulted in a greater than 50% reduction in complications related to vaginal bacteria. 5 In another retrospective study of a gynecologic oncology population, Avila et al found that a single dose of preoperative vaginal metronidazole reduced the risk of pelvic (13%, 0%) and urinary infection (20%, 2.2%) after robotic radical hysterectomy. 4 In our analysis, we included urinary tract infections and then did a post hoc analysis removing these infections and still, there was no difference between groups.…”
Section: Discussionmentioning
confidence: 99%
“…3 To our knowledge, current data evaluating the efficacy of metronidazole as an adjunct to hysterectomy antibiotic prophylaxis stems mainly from non-randomized studies. [4][5][6] Infection or patient-reported issues of infection with a subsequent use of healthcare resources can become an economic burden to our healthcare system and negatively affects patient satisfaction. Therefore, the primary aim of this study was to evaluate if vaginal metronidazole use for 5 days prior to scheduled hysterectomy, decreased postoperative issues and/or infections.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%